Association between mitral annulus calcification and severity of coronary artery disease assessed by SYNTAX score in patients presented with acute coronary syndrome - Esmailpour, Afsaneh; Nematollahi, Soroush; Hali, Reza; Sadeghian, Mohammad; Nayebirad, Sepehr; Vakili, Ahmad (Frontiers in Cardiovascular Medicine, 2024)
Objectives Mitral annulus calcification (MAC) has been linked to cardiovascular disease severity, but its relationship with the SYNTAX score (SS) in acute coronary syndrome (ACS) patients remains unclear. This study aimed to investigate the association between MAC and SS in ACS patients to explore the role of MAC in predicting cardiovascular disease severity. Methods We conducted a cross-sectional study of 233 ACS patients at Tehran Heart Center, Tehran, Iran, from December 2021 to August 2022. Patients with prior coronary artery disease (CAD) were excluded. Demographic data, risk factors, and medical history were extracted from clinical files. SS was determined using coronary angiography, and MAC was assessed via two-dimensional transthoracic echocardiography. Results The study population had a mean age of 58.79 years, with 74.7% male. MAC was present in 24.9% of participants, and 57% of those with MAC had an SS above 23. Univariate analysis revealed a significant association between MAC and higher SSs (odds ratio: 1.84, 95% CI: 1.02–3.39; P = 0.046). However, multivariable analysis showed that only left ventricular ejection fraction (LVEF) was independently associated with SS (odds ratio: 0.94, 95% CI: 0.89–0.99; P = 0.015). Conclusion While MAC was initially associated with higher SSs in ACS patients, only LVEF emerged as an independent predictor in the multivariable analysis. Although MAC may not be independently associated with SS, it may serve as a useful echocardiographic indicator of more severe CAD in ACS.